Important Residual Lesions and Early Unplanned Reinterventions After Pediatric Cardiac Surgery: A Scientific Statement From the American Heart Association - John M. Costello; Mjaye L. Mazwi; Christine M. Riley; Cesar E. Gonzalez de Alba; Laura J. Olivieri; Cynthia K. Rigsby; Kevin D. Hill; Emile Bacha; Jane W. Newburger; Meena Nathan (Circulation, 2026)
Optimal outcomes for congenital heart surgery depend on the expertise and judgment of an integrated multidisciplinary clinical team. The best outcomes require a comprehensive understanding of the patient’s anatomy and physiology, an appropriate therapeutic plan, a meticulously executed operation that is technically optimal and facilitated by lesion-specific anesthesia and perfusion strategies, and skilled perioperative care. A principal factor contributing to adverse outcomes is the presence of important residual lesions after surgery, which may necessitate early unplanned cardiac reinterventions during the index hospitalization. Such reinterventions occur in ≈5% of all pediatric cardiac operations, with a higher incidence in younger patients and more complex procedures. The presence of significant residual lesions and the need for unplanned reinterventions are strongly associated with increased morbidity, mortality, and resource use. Wide center-level variation in the incidence and timing of unplanned reinterventions suggests an opportunity for quality improvement. In this scientific statement, we summarize the incidence, risk factors, and clinical outcomes of important residual lesions and early unplanned cardiac reinterventions. We review postoperative monitoring strategies and clinical indicators suggestive of a residual lesion, and we provide an overview of the noninvasive imaging modalities used for their identification and quantification. The roles of diagnostic and interventional cardiac catheterization in the management of residual lesions are discussed, along with surgical considerations for early reoperation. We highlight the importance of communication with patients and families. Last, key areas for future investigations are identified.